2019
DOI: 10.2147/prom.s219166
|View full text |Cite
|
Sign up to set email alerts
|

<p>Correlations between patient-reported outcomes and self-reported characteristics in adults with hemophilia B and caregivers of children with hemophilia B: analysis of the B-HERO-S study</p>

Abstract: PurposePain, anxiety, depression, and other aspects of health-related quality of life (HRQoL) are important issues for people with hemophilia and caregivers of children with hemophilia. Patient-reported outcome (PRO) instruments may be used to assess aspects of HRQoL; however, the use of PROs in clinical management of patients with hemophilia is limited and inconsistent. The Bridging Hemophilia B Experiences, Results and Opportunities Into Solutions (B-HERO-S) study evaluated the impact of hemophilia B on HRQo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…34 When it comes to how hemophilia affects relationships, a research found that PWH reports negative experiences when telling friends about hemophilia and being bullied by peers due to hemophilia. 35 This was proven with reduced overall health and physical function and increased pain scores results from the study. Furthermore, 37% of young adults with hemophilia (YA-PWH) has impacted their ability to build intimate relationships with a partner or future partner and 36% of YA-PWH experienced negative outcomes upon telling their friends about having hemophilia.…”
Section: Psychosocial Impact On Hemophilia Patientsmentioning
confidence: 71%
See 2 more Smart Citations
“…34 When it comes to how hemophilia affects relationships, a research found that PWH reports negative experiences when telling friends about hemophilia and being bullied by peers due to hemophilia. 35 This was proven with reduced overall health and physical function and increased pain scores results from the study. Furthermore, 37% of young adults with hemophilia (YA-PWH) has impacted their ability to build intimate relationships with a partner or future partner and 36% of YA-PWH experienced negative outcomes upon telling their friends about having hemophilia.…”
Section: Psychosocial Impact On Hemophilia Patientsmentioning
confidence: 71%
“…Another reason could be due to the relationship issues of YA-PWH with their friends or partners. 35,36 More than 50% of adult respondents reported of mild or worse depression. Adults with hemophilia reported with 41% of moderate to severe depression/anxiety.…”
Section: Psychosocial Impact On Hemophilia Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, confirming previous studies, the HRQoL appears to have an inverse correlation with most psychological symptoms, such as anxiety, phobic anxiety, depression, obsessions and compulsions, interpersonal hypersensitivity, and somatic complaints. [3][4][5][28][29][30]35 Moreover, even the scores of paranoid ideation and psychoticism appear to have an inverse relationship with the HRQoL, highlighting the additional load of hostility, suspiciousness, withdrawal, and social isolation on the state of health. However, due to our study's small sample size, it is impossible to define the causal role of the symptoms on the deterioration of the HRQoL.…”
Section: Resultsmentioning
confidence: 99%
“…Most research agrees with the idea that specific factors in the medical history can determine a decline in specific components of HRQoL, such as physical activity, physical health, and social and interpersonal functioning. [2][3][4][5] Other studies underlined the role of factors such as work status and perceived physical pain.6,7 Nevertheless, many problems are still associated with older adults affected by age-related comorbidities (diabetes, cardiovascular and respiratory diseases, renal insufficiency, cancer, etc.) that require specialized medical and psychological interventions.…”
Section: Introductionmentioning
confidence: 99%